Modeling the Transport of Solar Energetic Particles in a Corotating Interaction Region - Y.-S. Zhong; G. Qin; S.-S. Wu (The Astrophysical Journal, 2024)
We present a new three-dimensional (3D) magnetohydrodynamic (MHD) model and a new 3D energetic particle transport (EPT) model. The 3D MHD model numerically solves the ideal MHD equations using the relaxing total variation diminishing scheme. In the 3D MHD simulations, we use simple boundary conditions with a high-speed flow, and we can clearly identify a corotating interaction region (CIR) with the characteristics of forward shock and reverse shock. The 3D EPT model solves the Fokker–Planck transport equation for the solar energetic particles (SEPs) using backward stochastic processes, with the magnetic field and solar wind velocity field from MHD results. For comparison, the 3D EPT model results with Parker fields are also obtained. We investigate the transport of SEPs with particle sources and observers in different positions in MHD fields with a CIR, and we compare the results with those in the Parker fields. Our simulation results show that the compression region with local enhancement of the magnetic field, i.e., CIR, can act as a barrier to scatter energetic particles back, and particles can struggle to diffuse through the strong magnetic field regions. Usually, a normal anisotropy profile is commonly present in SEP simulation results with Parker fields, and it is also typically present in that with MHD fields. However, because of the compression region of the magnetic field, energetic particles may exhibit anomalous anisotropy. This result may be used to replicate the spacecraft observation phenomena of the anomalous anisotropy.